The Contestation of Authority Among Traditional Leaders in Sungai Penuh City in Determining the Direction of the Qibla - Darlius, Darlius; Susanti, Susi (STAIN MAJENE, 2025)
This study examines the differences among traditional leaders in determining the direction of the qibla for public cemeteries of indigenous communities in the village of Hamparan Rawang, Sungai Penuh City. Traditional leaders claim that their respective communities' graves face the correct direction of the qibla. The purpose of this study is to explain the causes of these differences and the methods used to determine the direction of the qibla for cemeteries. This study uses a qualitative method with data collection techniques through observation, interviews, and literature review with descriptive analysis. The results of this study indicate that the cause of the contestation between indigenous groups is due to several factors, namely differences in customs, ideology, and interpretation of religious values towards culture. In determining the direction of the qibla, traditional leaders only use two methods, namely: first, referring to the graves of ancestors or previous graves. Second, following the direction of the nearest mosque.